‘Not Designed For Us’ A Visual Exploration of Spatial Use Patterns in Remote Aboriginal Domiciliary Environments - Farley, Holly Rose (Curtin University, 2018)
This thesis explores domiciliary spatial use within remote Western Australian Aboriginal communities. It explores relationships between culture and built environments, concerning the relationship between domiciliary environments and sociocultural spatial behaviours. It aims to investigate continuities of domiciliary spatial use between traditional camp settings and Western European housing. A method is developed for architects to design for cultures other than their own, which is revelatory of the sociocultural principles governing spatial use in domiciliary environments.